Intensive walking exercise for lower extremity peripheral arterial disease: A systematic review and meta‐analysis. (21st July 2015) - Lyu, Xiafei; Li, Sheyu; Peng, Shifeng; Cai, Huimin; Liu, Guanjian; Ran, Xingwu
Abstract: Background: Supervised treadmill exercise is the recommended therapy for peripheral arterial disease (PAD) patients with intermittent claudication (IC). However, most PAD patients do not exhibit typical symptoms of IC. The aim of the present study was to explore the efficacy and safety of intensive walking exercise in PAD patients with and without IC. Methods: The PubMed, Embase and Cochrane Library databases were systematically searched. Randomized controlled trials comparing the effects of intensive walking exercise with usual care in patients with PAD were included for systematic review and meta‐analysis. Results: Eighteen trials with 1200 patients were eligible for the present analysis. Compared with usual care, intensive walking exercise significantly improved the maximal walking distance (MWD), pain‐free walking distance, and the 6‐min walking distance in patients with PAD ( P  < 0.00001 for all). Subgroup analyses indicated that a lesser improvement in MWD was observed in the subgroup with more diabetes patients, and that the subgroup with better baseline walking ability exhibited greater improvement in walking performance. In addition, similar improvements in walking performance were observed for exercise programs of different durations and modalities. No significant difference was found in adverse events between the intensive walking and usual care groups (relative risk 0.84; 95% confidence interval 0.51, 1.39; P  = 0.50). Conclusions: Regardless of exercise length and modality, regularly intensive walking exercise improves walking ability in PAD patients more than usual care. The presence of diabetes may attenuate the improvements in walking performance in patients with PAD following exercise.